2009
DOI: 10.2147/vhrm.s3302
|View full text |Cite
|
Sign up to set email alerts
|

Fixed combination of irbesartan and hydrochlorothiazide in the management of hypertension

Abstract: Approximately 25% of the adult population worldwide is hypertensive and thus at risk of cardiovascular morbidity and mortality. Despite the availability of many antihypertensive drugs, at least 50% of patients do not achieve blood pressure (BP) targets and thus remain at increased cardiovascular risk. Fixed-dose (FD) irbesartan/hydrochlorothiazide (HCTZ) is an antihypertensive combination therapy approved for the treatment of patients whose BP is not adequately controlled on monotherapy and for initial treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
4
11
0
Order By: Relevance
“…15 A range of studies has shown that the higher the initial value, the higher the achievable reduction in blood pressure 16,17 or the more common is the normalization of blood pressure after the start of therapy [16][17][18][19] (see also Figure 4). This might be related to a regression to the mean phenomenon in single patients but certainly not in the majority of patients in this study of more than 8123 patients.…”
Section: Predictor Of Reduction In Blood Pressurementioning
confidence: 99%
“…15 A range of studies has shown that the higher the initial value, the higher the achievable reduction in blood pressure 16,17 or the more common is the normalization of blood pressure after the start of therapy [16][17][18][19] (see also Figure 4). This might be related to a regression to the mean phenomenon in single patients but certainly not in the majority of patients in this study of more than 8123 patients.…”
Section: Predictor Of Reduction In Blood Pressurementioning
confidence: 99%
“…In several observational studies, fixed-dose combinations were associated with higher rates of compliance, persistence, and adherence to treatment regimens 75–82. A meta-analysis of 15 published studies with a total of 32,331 patients concluded that fixed-dose combinations of antihypertensive agents were associated with increased compliance and no changes in the frequency of adverse events when compared with free drug components given separately 80…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that during long-term therapy, thiazides act by reducing total peripheral resistance probably through a direct vascular effect. Thiazides reduce water reabsorption in the distal convoluted tubules and thereby diminish plasma volume and cardiac output (Bramlage, 2009;Raheja et al, 2012).…”
Section: Antihypertensive Drugsmentioning
confidence: 99%